The last of the Mohicans ([Burbank, CA] : Warner Bross, 1992)
A love story set during the French and Indian War, between an American raised by the Mohican Indians and the daughter of a British officer
Title from title screen
Adapted from the novel by James Fenimore Cooper
Based on the 1936 movie screenplay by Philip Dunne
Special features: All new dolby digital 5.1 soundtrack remastered for home theatres, dolby digital 5.1 music-onlu audio track, interactive menus theatrical trailers, scene access
DVD format
Dolby Digital
Keywords: Cooper, James Fenimore, -- 1789-1851 -- Film and video adaptations; Mohegan Indians -- Drama; Man-woman relationships -- Drama; United States -- History -- French and Indian War, 1755-1763 -- Drama